Malic acid: A novel processing aid for thermoplastic starch/poly(butylene adipate‐co‐terephthalate) compounding and blown film extrusion. Issue 48 (22nd August 2017) - Fahrngruber, Barbara; Siakkou, Eleni; Wimmer, Rupert; Kozich, Martin; Mundigler, Norbert
ABSTRACT: The processing of polysaccharide‐based polymer compounds represents a major challenge because these materials behave considerably different compared to their petro‐based counterparts. Especially in the manufacture of thermoplastic starch (TPS)–polyester films by means of blown film extrusion, an increase in the natural material proportion generally leads to processing difficulties. In addition, higher TPS contents adversely affect mechanical material characteristics. The present study focuses on the effect of malic acid (MA) on processing parameters and on the quality of TPS/poly(butylene adipate‐ co ‐terephthalate) films. The MA enantiomersd (+) andl (–) as well as the racemate were applied at various concentrations (0.2, 0.4, and 0.8 wt %). Results indicate that the addition of racemic MA at concentrations of 0.2% and 0.4% significantly improved the processibility of TPS. Simultaneously, positive effects such as improved ductility and water sorption characteristics were found. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45539. Abstract :